Virtual property in the digital age: legal nature and regulatory approaches - Yakubov Akhtam Nusratullaevich (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
What should be the legal mechanisms for the protection of user rights in relation to virtual property, there is no uniform approach to the question of which direction countries should take. Currently, there is no uniform approach to the protection of the user's rights to virtual game property in world jurisprudence. In vertical relations, that is, when considering disputes arising from the relationship between the developer and the user, the courts in most cases prefer to apply the theory of natural obligations and the theory of service provision. In many countries, the transaction of virtual property is not legally regulated. The transfer of virtual game property is considered the transfer of rights of claim to the virtual property by the developer of the game to the participant. The author analyzed the legal description of virtual property, which is considered one of the objects of the digital world, based on national and foreign experience, and analyzed the need to find them as a separate independent object in civil legislation.